2018
DOI: 10.5194/acp-18-10355-2018
|View full text |Cite
|
Sign up to set email alerts
|

Online gas- and particle-phase measurements of organosulfates, organosulfonates and nitrooxy organosulfates in Beijing utilizing a FIGAERO ToF-CIMS

Abstract: Abstract. A time-of-flight chemical ionization mass spectrometer (CIMS) utilizing the Filter Inlet for Gas and Aerosol (FIGAERO) was deployed at a regional site 40 km north-west of Beijing and successfully identified and measured 17 sulfur-containing organics (SCOs are organo/nitrooxy organosulfates and sulfonates) with biogenic and anthropogenic precursors. The SCOs were quantified using laboratory-synthesized standards of lactic acid sulfate and nitrophenol organosulfate (NP OS). The variation in field obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 72 publications
5
72
1
1
Order By: Relevance
“…The laboratory setup on the Changping University campus of Peking University was situated at a semi-rural site 40 km northwest of Beijing close to Changping (40.2207 • N, 116.2312 • E). The general setup has previously been described by Le Breton et al (2018).…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The laboratory setup on the Changping University campus of Peking University was situated at a semi-rural site 40 km northwest of Beijing close to Changping (40.2207 • N, 116.2312 • E). The general setup has previously been described by Le Breton et al (2018).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Gas-and particle-phase ambient species were measured using an iodide ToF-CIMS (resolving power of 3500) coupled to the FIGAERO inlet (Lopez-Hilfiker et al, 2014). The setup for this campaign has previously been described by Le Breton et al (2018). Briefly, the iodide ionisation scheme was utilised to acquire non-fragmented ions of interest by passing ultra-high-purity N 2 over a permeation tube containing liquid CH 3 I (Alfa Aesar, 99 %) and through a Tofwerk X-ray ion source type P (operated at 9.5 kV and 150 µA) to produce the iodide reagent ions.…”
Section: Tof-cims Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent measurements close to Beijing using a Filter Inlet for Gas and Aerosol (FIGAERO) chemical ionization mass spectrometer (CIMS) have shown that sulfur containing organic compounds, such as organo/nitrooxy organosulfates and sulfonates, can also be present in the gas-phase (Le Breton et al, 2018). Higher temperatures promote the presence of sulfur compounds in the gas phase and furthermore the partitioning to the particle phase was found to be dependent on ambient relative humidity.…”
Section: Introductionmentioning
confidence: 99%
“…In urban areas, such as Xi'an in northwestern China, organosulfates are primarily of anthropogenic origin (Huang et al, 2018), but already in semi rural locations 40 km northwest of Beijing, up to 19% of the sulfur containing organics have been identified to be of biogenic origin (Le Breton et al, 2018).…”
Section: Introductionmentioning
confidence: 99%